Analysis Of The Utilization Of The Merdeka Mengajar Platform (Pmm) In The Implementation Of The Merdeka Curriculum - Marzoan, Marzoan (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to analyze the improvement in the quality of utilizing the Merdeka Mengajar Platform (PMM) to support the implementation of the Merdeka Curriculum in independent educational units. PMM is a learning platform designed to facilitate teachers and schools in optimizing competency-based learning processes. The study was conducted in the West Nusa Tenggara (NTB) Province, covering ten districts/cities: Kota Mataram, Kota Bima, Kabupaten Lombok Barat, Kabupaten Lombok Timur, Kabupaten Lombok Utara, Kabupaten Lombok Tengah, Kabupaten Sumbawa, Kabupaten Sumbawa Barat, Kabupaten Dompu, and Kabupaten Bima. The research was carried out from February 2024 to November 2024. Using a descriptive quantitative approach, data were collected through surveys, interviews, and document analysis from 6,495 educational units implementing the Merdeka Curriculum. The sample was selected using stratified random sampling, involving 650 educational units to ensure representation across various educational levels and geographic locations.The results show that 76.5% of independent educational units actively utilize PMM, particularly in improving student learning progress and using teaching tools. Supporting factors include continuous training, school leadership support, and the active involvement of teachers in integrating PMM into lesson plans. However, challenges such as limited internet access in remote areas remain significant obstacles. Additionally, the study found that the establishment of learning communities, both within schools and between schools, has been a notable achievement, although mentoring and the role of school supervisors in optimizing these communities need further improvement.This study concludes that the optimal use of PMM can support the successful implementation of the Merdeka Curriculum, especially in enhancing the quality of teaching and student learning outcomes. Key recommendations include strengthening educational technology infrastructure, developing offline tools, providing continuous teacher training, and optimizing mentoring for learning communities and the role of school supervisors to ensure the sustainability of this program.